An improved path flux analysis with multi generations method for mechanism reduction. Issue 2 (3rd March 2016) - Wang, Wei; Gou, Xiaolong
Abstract : An improved path flux analysis with a multi generations (IMPFA) method is proposed to eliminate unimportant species and reactions, and to generate skeletal mechanisms. The production and consumption path fluxes of each species at multiple reaction paths are calculated and analysed to identify the importance of the species and of the elementary reactions. On the basis of the indexes of each reaction path of the first, second, and third generations, the improved path flux analysis with two generations (IMPFA2) and improved path flux analysis with three generations (IMPFA3) are used to generate skeletal mechanisms that contain different numbers of species. The skeletal mechanisms are validated in the case of homogeneous autoignition and perfectly stirred reactor of methane and n-decane/air mixtures. Simulation results of the skeletal mechanisms generated by IMPFA2 and IMPFA3 are compared with those obtained by path flux analysis (PFA) with two and three generations, respectively. The comparisons of ignition delay times, final temperatures, and temperature dependence on flow residence time show that the skeletal mechanisms generated by the present IMPFA method are more accurate than those obtained by the PFA method, with almost the same number of species under a range of initial conditions. By considering the accuracy and computational efficiency, when using the IMPFA (or PFA) method, three generations may be the best choice for the reduction of large-scale detailed chemistry.